Epigenetic regulation of transcription: a mechanism for inducing variations in phenotype (fetal programming) by differences in nutrition during early life? - Burdge, Graham C.; Hanson, Mark A.; Slater-Jefferies, Jo L.; Lillycrop, Karen A. (British journal of nutrition, 2007)
There is considerable evidence for the induction of different phenotypes by variations in the early life environment, including nutrition, which in man is associated with a graded risk of metabolic disease; fetal programming. It is likely that the induction of persistent changes to tissue structure and function by differences in the early life environment involves life-long alterations to the regulation of gene transcription. This view is supported by both studies of human subjects and animal models. The mechanism which underlies such changes to gene expression is now beginning to be understood. In the present review we discuss the role of changes in the epigenetic regulation of transcription, specifically DNA methylation and covalent modification of histones, in the induction of an altered phenotype by nutritional constraint in early life. The demonstration of altered epigenetic regulation of genes in phenotype induction suggests the possibility of interventions to modify long-term disease risk associated with unbalanced nutrition in early life.